Role of Management Support in Driving Employees’ Quality Control Practices - Ifeanyichukwu Edeh; Martins Chibuzor Akaeze (Journal Majelis Paspama, 2025)
Quality control remains a fundamental driver of organizational performance, yet its success often depends on the extent of management support. In contemporary business environments, where customer satisfaction and competitiveness hinge on product and service quality, managerial involvement has become indispensable. This study investigated the role of management support in driving employees’ quality control practices. This study employed a survey research design, using questionnaires to gather data from a sample of 98 respondents, determined from a population of 130 using Yamane’s (1967) formula. The questionnaire method ensured the collection of reliable facts and figures for analyzing research questions and testing hypotheses. Data analysis involved simple percentage calculations to compare response trends and draw logical conclusions. Hypothesis testing was conducted using the Chi-square (χ²) statistical tool at a 5% significance level and 4 degrees of freedom. The decision rule specified rejecting the null hypothesis when χ² calculated exceeded the critical value, thereby accepting the alternative hypothesis. The results show strong agreement among respondents that management support influences employee commitment to quality control. A majority (74 respondents; 75.51%) strongly agreed, while only a small proportion disagreed (5.10%). Chi-square analysis further confirmed significance, with a calculated value (192.51) exceeding the table value (9.49), leading to acceptance of the alternative hypothesis that management support drives seriousness in quality control. Gender differences were evident: most males strongly agreed (68), while females showed more variation, with some selecting agree (13) or undecided (6). Association measures such as Phi (.857) and Cramer’s V (.857) confirmed strong relationships, though negative ordinal correlations highlighted divergent response patterns. Gender-based variations were also observed, with male respondents showing higher consensus compared to females. The study concludes that managerial presence, incentives, and commitment to quality strongly shape employees’ adherence to quality standards, ultimately boosting organizational effectiveness and customer satisfaction. It recommends sustained managerial engagement to foster a culture of continuous quality improvement.